Worthy : [a novel] - Hyde, Catherine Ryan (Lake Union Publishing, 2015)
Virginia finally had the chance to explore a relationship with Aaron when he asked her on a date. She had been waiting, hoping that the widower and his young son, Buddy, would welcome her into their lives. But a terrible tragedy strikes on the night of their first kiss, crushing their hopes for a future together. Nineteen years later, Virginia is engaged, though she has not forgotten Aaron or Buddy. When her dog goes missing and it comes to light that her fiance set him loose, a distraught Virginia breaks off the engagement and is alone once again. A shy young man has found the missing pet, and although he's bonded with the animal, he answers his conscience and returns the dog. Before long, Virginia and the young man discover a connection from their pasts that will help them let go of painful memories and change their lives forever.